Associations Among Sleep Latency, Subjective Pain, and Thermal Pain Sensitivity in Gynecologic Cancer. Issue 1 (27th November 2018) - Kirsch, Janae L; Robinson, Michael E; McCrae, Christina S; Kacel, Elizabeth L; Wong, Shan S; Patidar, Seema; Sannes, Timothy S; Garey, Stephanie; Castagno, Jacqueline C; Pereira, Deidre B
Abstract: Objective: Pain is common among women with gynecologic cancer and contributes to depressed mood, sleep disturbances, and likelihood of future chronic pain. Little is known about how psychosocial factors are associated with central sensitization of pain in gynecologic cancer. This study examined relations among depressive symptoms, sleep, subjective pain, and aftersensation pain (a proxy for central sensitization of pain) in gynecologic cancer. Methods: Participants were 42 women (mean age [SD] = 59.60 [10.11] years) enrolled in a randomized clinical trial examining psychological intervention effects on sleep, pain, mood, and stress hormones/cytokines in gynecologic cancer. Six to eight weeks after surgery, participants completed an assessment of depressive symptoms, sleep, and subjective pain and a temporal summation of pain protocol via quantitative sensory testing (QST). Results: Controlling for recent chemotherapy, history of chronic pain, and analgesic medication use, regression analyses revealed that longer sleep onset latency (SOL; B  = 3.112, P  = 0.039, bias-corrected and accelerated (BCa) 95% confidence interval [CI] = 0.371 to 6.014) and greater sensory pain ( B  = 0.695, P  = 0.023, BCa 95% CI = 0.085 to 1.210) were associated with greater aftersensation pain at 15 seconds. Greater sensory pain scores were associated with greater aftersensation pain at 30 seconds ( B  = 0.286, P  = 0.045, BCa 95% CI = 0.008 to 0.513). Depression was not associated with aftersensation pain. The overall models accounted for 44.5% and 40.4% of the variance in aftersensation pain at 15 and 30 seconds, respectively. Conclusions. Longer SOL and higher subjective sensory pain were related to greater aftersensation of experimentally induced pain in women postsurgery for gynecologic cancers. Interventions that improve sleep and subjective sensory pain during the perisurgical period may reduce risk for central sensitization of pain.